2008
DOI: 10.1021/jp802773r
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Synthesis of Stable Zerovalent Metal Nanoparticles under Standard Reaction Conditions

Abstract: In this report is discussed a novel, easy, and general synthesis method to prepare zerovalent iron (ZVI) and copper (ZV Cu) nanoparticles (NPs), from colloid dispersions in an environmental friendly organic solvent, ethylene glycol (EG). Conventional metallic salts are used as nanoparticle precursors; sodium borohydride (NaBH4) is the reducing agent, and triethylamine (TEA) is used as the nanoparticle stabilizer. The chemical changes take place instantaneously under normal reaction conditions. Small iron (alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 101 publications
0
26
0
Order By: Relevance
“…36 In the case of monometallic Cu NPs, the prevailing structure-type noted has hitherto been Cu(core) @CuO/Cu 2 O(shell), 37 with efforts to control the formation of an oxide shell predicated on the use of capping agents that inhibit molecular access to the particle surface. [38][39][40] More recently, it has been shown that the use of polymeric capping agents may enhance the oxidative stability of NPs whilst permitting substrate access and efficient catalysis. 41 Moreover, the range of polymers available for stabilizing highly reactive main group nanomaterials has also very recently been extended through the use of poly(methyl methacrylate) (PMMA) to protect Mg nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…36 In the case of monometallic Cu NPs, the prevailing structure-type noted has hitherto been Cu(core) @CuO/Cu 2 O(shell), 37 with efforts to control the formation of an oxide shell predicated on the use of capping agents that inhibit molecular access to the particle surface. [38][39][40] More recently, it has been shown that the use of polymeric capping agents may enhance the oxidative stability of NPs whilst permitting substrate access and efficient catalysis. 41 Moreover, the range of polymers available for stabilizing highly reactive main group nanomaterials has also very recently been extended through the use of poly(methyl methacrylate) (PMMA) to protect Mg nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Other characterizations of ZV iron NPs were published [17]. Table 1 summarizes the calculated parameters of the ZVI dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the calculated parameters of the ZVI dispersion. These parameters were calculated considering the particle size distribution, assuming a completed reaction (excess of NaBH 4 was used) and spherical particles, see reference [17] for details. Parameters in Table 1 correspond to the ZVI NPs obtained in a typical synthesis as described in the Materials and Methods section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of different approaches have been employed to protect this sensitive material from oxidation, where commonly used methods include coating with carbon [19,22], silica [23], noble metals and oxides [24][25][26], or the utilization of different surfactants and stabilizers [27]. However, none of these approaches lead to covalent grafting.…”
Section: Introductionmentioning
confidence: 99%